Evaluation of Scan Rate Influence on Cyclic Voltammograms of Copper Electrodes Coated with PS-CS-GA/ZnO Nanocomposite - Murniati, Anceu; Nur, Ilahi Hidayanti; Gumelar, Niki; Budiman, Senadi; Buchari, Buchari; Gandasasmita, Suryo; Nurachman, Zeily (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2024)
Copper (Cu) is widely utilized as an electrode material due to its high conductivity and relatively low cost. This study aims to develop nanocomposite-modified Cu electrodes using polysulfone (PS), chitosan (CS), glutaraldehyde (GA), and zinc oxide (ZnO) to form PS-CS-GA/ZnO-NP modified Cu electrodes. The nanocomposite was prepared in the proportions of 48.8% PS, 24.4% CS, 24.4% ZnO, and 2.4% GA using the phase inversion method. The characterization of the PS-CS-GA/ZnO nanocomposite-modified Cu electrode was conducted using cyclic voltammetry with a 0.01 M K3[Fe(CN)6] in 0.1 M KCl. The cyclic voltammogram profile was obtained at a scan rate of 25 mV/s, exhibiting an ipa/ipc ratio of 0.93 within a potential of -1.5 to +0.4 V vs Ag/AgCl over 15 cycles. The FTIR spectrum of the PS-CS-GA/ZnO nanocomposite thin film displayed a peak at 1668 cm-1, indicating the presence of C=N groups, which suggests a cross-linking interaction between CS and GA.